Gas exchange of Eucalyptus camaldulensis Dehnh under saline water influence - Zapelini, Gabriel; Navroski, Marcio Carlos; Pereira, Mariane de Oliveira; Andrade, Tiago Krischnegg de; Baptista, Karollyne Renata Silva de Paula; Andrade, Ramon Silveira de (Revista Ecologia e Nutrição Florestal - ENFLO, 2020)
In view of the increasing expansion of the use of wood and non-timber products from the Eucalyptus genus, the identification and impact caused by the salinity of Brazilian soils in the development and growth of the species are of fundamental importance for a better utilization of salinized areas in the country. In order to contribute to the understanding of this problem, the present work evaluated the effect of different levels of salinity (brackish water) on gas exchange in Eucalyptus camaldulensis Dehnh plants. The levels analyzed were: 0, 50, 100, 200, 400 µM NaCl. A completely randomized design with 10 replicates (plants) was used, in which the gaseous exchanges were evaluated with the aid of a portable photosynthesis meter (IRGA), determined the values of photosynthesis (A), stomatal conductance (gs), rate transpiration (E), the relation between the intercellular and atmospheric concentration of CO² (Ci / Ca) and water use efficiency (WUE). Initially the seedlings did not undergo physiological changes, showing a certain tolerance of the species to high levels of salinity. Reduction in gas exchanges was only more noticeable after reapplication of the salt (after 7 days). Due to the results obtained, high tolerance of the species to salinity is observed.